Temporal lobe epilepsy due to meningoencephaloceles into the greater sphenoid wing: a consequence of idiopathic intracranial hypertension? - Urbach, H.; Jamneala, G.; Mader, I.; Egger, K.; Yang, S.; Altenmüller, D. (Neuroradiology, 2018)
Purpose: Antero-inferior temporal lobe meningoencephaloceles are a rare, but increasingly recognized cause of drug-resistant temporal lobe epilepsy (TLE). In order to evaluate whether these lesions are related to idiopathic intracranial hypertension (IIH), we analyzed clinical and MRI findings of a cohort of patients undergoing presurgical work-up. Methods: Seizure onset in the anterior temporal lobe was proven by EEG electrodes in 22 patients, and in 21 patients, anterior temporal lobectomy (mostly with sparing of the hippocampus) was performed. MRI signs of IIH (in particular empty sella) and the volumes of the ventricles and external CSF spaces were determined and related to the body mass index (BMI) and clinical outcome. Results: Six of seven obese (BMI > 30 kg/m) compared to four of 15 non-obese patients had partial empty or empty sella ( p = 0.007). Bilateral lesions were found in all obese and 11 patients. Seizure freedom (Engel class 1A) was achieved in 12 of 21 patients (5 obese compared to 7 non-obese patients). BMI was related to the volume of the external CSF spaces ( r = 0.467), and age at seizure onset was higher in obese patients. Conclusion: Roughly a third of patients with temporal lobe epilepsy due to antero-inferior meningoencephaloceles is obese and has MRI signs of idiopathic intracranial hypertension.